Properties of Natural Rubber-Based Composites Containing Fullerene - Omar A. Al-Hartomy; Ahmed A. Al-Ghamdi; Falleh Al-Salamy; Nikolay Dishovsky; Desislava Slavcheva; Farid El-Tantawy (International Journal of Polymer Science)
In this study the influence of fullerenes in concentrations from 0.5 to 1.5 phr on both the vulcanization characteristics of the compounds and physicomechanical, dynamic, and dielectric properties and thermal aging resistance of nanocomposites on the basis of natural rubber has been investigated. The effect of the filler dispersion in the elastomeric matrix has been also investigated. Neat fullerene and the composites comprising it have been studied and characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM).